Pediatric Intracochlear Schwannoma: Case Series and Review of the Literature - Enrico Liaci; Maurizio Negri; Francesco Maccarrone; Silvia Piccinini; Enrico Pasanisi; Andrea Bacciu; Filippo Di Lella (Journal of International Advanced Otology)
Background: Intracochlear schwannomas (ICSs) are a subtype of intralabyrinthine schwannomas, completely located in the cochlear lumen. ICSs are particularly rare in the pediatric population. Putative diagnosis is made on the basis of magnetic resonance findings with signal characteristics that should remain the same at follow-up imaging.